Production, Supply and Circulation of 'National' Gold Coins in Brazil (1720-1807) - Lima, Fernando Cerqueira (2015)
Based on the hypotheses that Brazil was not merely an economy that exported precious metals and that there was a relative expansion of the domestic market, in this paper we assess the production, supply and circulation of ʻnationalʼ gold coins in Brazil in the 18th century. New estimates are provided of the production of these gold coins at the mints of Rio de Janeiro, Bahia and Minas Gerais. Comparing the values of the coinage with remittances to Lisbon, the first half of the 18th century reveals a more stable conjuncture than was found in the second half. This latter period shows fluctuations that were expressed in the faster growth of the supply despite the fall that took place in the production/coinage of gold. Our conclusions question the historiographical theses about the shortage of currency in Brazil throughout the 18th century. The growth of the economy from the last quarter of the century onwards implied an increase in the demand for money, which it proved possible to meet through the production of ʻnationalʼ gold coins.